Generosity Maxim in Leech's Theory in Pshdar Area: Socio-Pragmatic Perspective (Raparin Journal of Humanities (RJH), 2021)
This paper is entitled ‘’Generosity Maxim in Leech's Theory in Pshdar Area: Socio-Pragmatic Perspective, which aims at showing generosity among individuals including showing generosity in this specific area for the purpose of finding out its roots people, because generosity maxim is minimizing self to others, and indicating such  factors as religion, education , non-education, and gender affect the utterance. The principles of politeness which have been recognized by Leech are the Maxim of Tact, the Maxim of Generosity, the Maxim of Modesty, the Maxim of approbation, the Maxim of Agreement, and the Maxim of Sympathy. It is important to bear in mind that this theory focuses on individual face, there are various face threatening acts, for instance the threat can be assumed to the hearer or to the speaker.   This paper conducts a survey of Pshdaryan district through using a questionnaire as a quantitative method for the purpose of data collection. The participants of this study are the people of Pshdar area who are 162 participants from different classes, genders, educational background, age, and occupation.   The result of the study showed that generosity is the main reason behind using both direct and indirect offers and invitations. Besides, it showed that the cost-benefit scale can explain the politeness utterance raised in performing these speech acts Finally, it is recommended that other politeness principle maxims are tested in Kurdish culture to know the level of the maxims practically.